Effect of the one-day fasting on cortisol and DHEA daily rhythm regarding sex, chronotype, and age among obese adults - Marciniak, Martyna; Sato, Maki; Rutkowski, Rafał; Zawada, Agnieszka; Juchacz, Aldona; Mahadea, Dagmara; Grzymisławski, Marian; Dobrowolska, Agnieszka; Kawka, Edyta; Korybalska, Katarzyna; Bręborowicz, Andrzej; Witowski, Janusz; et al. (Frontiers in Nutrition, 2023)
Physiological and biochemical processes in the human body occur in a specific order and show rhythmic variability. Time dependence characterizes the secretion of cortisol and dehydroepiandrosterone (DEHA). One-day fasting implies alternating fasting days and eating days. The study aimed to determine how one-day fasting affects the daily rhythm of cortisol and DHEA levels in obese people with the effect of sex and chronotype. Forty-nine obese patients (BMI 32.2-67.1 kg/m2; 25 women and 24 men) underwent a three-week hospital-controlled calorie restriction diet to reduce body weight. During hospitalization, patients fasted for one day, during which only water could be consumed. Samples of whole mixed unstimulated saliva were collected at 3-h intervals over a 72-h period and analyzed for cortisol and DHEA by immunoassays. The individual chronotypes were assessed by the morning and evening questionnaire, according to Horne and Östberg. Three components of daily rhythm were evaluated: amplitude, acrophase, and the so-called MESOR. Cortisol rhythm showed differences in the amplitude (p = 0.0127) and acrophase (p = 0.0005). The amplitude on the fasting day was 11% higher (p = 0.224) than the day after. The acrophase advanced on the day of fasting, 48 minutes earlier than the day before (p = 0.0064), and by 39 minutes to the day after fasting (p = 0.0005). In the rhythm of DHEA, differences were found in the MESOR (p= 0.0381). The MESOR on the fasting day increased. Our results obtained during 72 consecutive hours of saliva sampling suggest that one-day fasting may affect three components of cortisol and DHEA daily rhythm. Additionally, no differences were found in the daily rhythm between the morning and evening chronotypes and between females and males. To the best of our knowledge, this is the first presentation of changes in DHEA rhythm during one-day fasting.